Dominance, Interruption, and Corrective Strategic Rebalancing Under Market Volatility - Ahmad Mundzir (Manexia: Journal of Business, Management, and Creative Economy, 2025)
Market volatility frequently exposes structural imbalances that accumulate during periods of sectoral or strategic dominance. While prior research has examined diversification and strategic scope largely through structural or performance lenses, limited attention has been given to the endogenous processes through which dominance emerges, stabilizes, and is subsequently disrupted. This conceptual paper develops a process theory explaining how strategic dominance forms through recursive reinforcement, how volatility acts as an interruption mechanism that reveals latent imbalance, and how organizations engage in corrective strategic rebalancing. The framework conceptualizes dominance as an internally reinforced concentration of strategic attention and resource allocation, rather than merely an external market outcome. Volatility functions not simply as exogenous shock but as a revelatory condition that activates managerial interpretation and strategic recalibration. Corrective rebalancing is theorized as a disciplined, governance-mediated response aimed at restoring coherence and long-term viability. By integrating strategic management, managerial cognition, and governance perspectives, the paper advances a dynamic account of how organizations oscillate between dominance and balance. The study contributes to strategy theory by reframing imbalance as an endogenous process and positioning corrective rebalancing as a core mechanism of strategic resilience under persistent uncertainty.